2013
DOI: 10.1245/s10434-013-2949-y
|View full text |Cite
|
Sign up to set email alerts
|

S-100B: A Stronger Prognostic Biomarker than LDH in Stage IIIB–C Melanoma

Abstract: The S-100B level measured preoperatively is, in contrast to LDH, one of the most important independent predictors of melanoma prognosis in patients undergoing TLND for nodal macrometastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 28 publications
3
37
0
Order By: Relevance
“…This was confirmed by our observation of increased melanin corpuscles by electron microscopy. S-100B and MIA are widely used as biomarkers for melanoma [24][25][26][27]. In our study, the expression of both S-100B and MIA was significantly decreased in B16-F1 cells after treatment with CMSP, which suggested a mitigation of their malignant phenotype.…”
Section: Discussionsupporting
confidence: 52%
“…This was confirmed by our observation of increased melanin corpuscles by electron microscopy. S-100B and MIA are widely used as biomarkers for melanoma [24][25][26][27]. In our study, the expression of both S-100B and MIA was significantly decreased in B16-F1 cells after treatment with CMSP, which suggested a mitigation of their malignant phenotype.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, recent data shows that treatment monitoring in patients with SCLC might be optimized using ProGRP and NSE as TMs [40]. Based on the same concept, the addition of nucleic acids (e.g., ctDNA) might help in closing the diagnostic gap in tumors without known TMs (e.g., sarcomas) or in combination improve the monitoring of malignancies with less established TMs (e.g., S-100B in melanomas [79, 80]) Further ongoing novel marker research will hopefully add to our current armamentarium of available TM.…”
Section: Future Directionsmentioning
confidence: 99%
“…S100B was also linked to inflammation since it interacts with the activated leukocyte cell adhesion molecule (ALCAM) and mediates NF-kB signaling, in a time and dose-dependent manner 78 . Another study brought evidence that circulatory S100B could pinpoint with a better precision than LDH, the poor prognosis in stage IIIB-C melanoma patients 79 . Our previously published results have shown that in adult melanoma patients, there is a strong correlation between S100B and melanoma inhibitory activity (MIA) and that this association matches an unfavorable clinical evolution.…”
Section: Circulatory Inflammatory Markersmentioning
confidence: 99%